The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-25563-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modelling of amino acid transport and homeostasis in mammalian cells

Abstract: Homeostasis is one of the fundamental concepts in physiology. Despite remarkable progress in our molecular understanding of amino acid transport, metabolism and signaling, it remains unclear by what mechanisms cytosolic amino acid concentrations are maintained. We propose that amino acid transporters are the primary determinants of intracellular amino acid levels. We show that a cell’s endowment with amino acid transporters can be deconvoluted experimentally and used this data to computationally simulate amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 64 publications
(73 reference statements)
6
44
1
Order By: Relevance
“…In the IC 50 determinations on hCMEC/D3 cells, the baseline uptake of [ 13 C 6 , 15 N]-L-leucine was considerably lower in the presence of BCH compared to JPH203. This is in accordance with the non-selective inhibitory effect of BCH for the LAT system [ 30 , 42 , 47 , 48 ] and other transporters such as B 0 AT2 [ 10 ], which may contribute to baseline uptake of [ 13 C 6 , 15 N]-L-leucine. Because the LAT-1 specific inhibitor JPH203 inhibits the majority of [ 13 C 6 , 15 N]-L-leucine uptake in hCMEC/D3 cells, it can be concluded that LAT-1 HD is the primary transporter responsible for L-leucine uptake in these brain capillary endothelial cells.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the IC 50 determinations on hCMEC/D3 cells, the baseline uptake of [ 13 C 6 , 15 N]-L-leucine was considerably lower in the presence of BCH compared to JPH203. This is in accordance with the non-selective inhibitory effect of BCH for the LAT system [ 30 , 42 , 47 , 48 ] and other transporters such as B 0 AT2 [ 10 ], which may contribute to baseline uptake of [ 13 C 6 , 15 N]-L-leucine. Because the LAT-1 specific inhibitor JPH203 inhibits the majority of [ 13 C 6 , 15 N]-L-leucine uptake in hCMEC/D3 cells, it can be concluded that LAT-1 HD is the primary transporter responsible for L-leucine uptake in these brain capillary endothelial cells.…”
Section: Discussionsupporting
confidence: 78%
“…The first, JPH203, is currently studied in a clinical trial and shows high specificity for LAT-1 HD [ 24 , 31 ]. The second, BCH, is a non-selective inhibitor for L-system amino acid transporters and a substrate of LAT-1 [ 30 ], LAT-2 [ 42 ], LAT-3 [ 47 ], and LAT-4 [ 48 ], as well as other amino acid transporters such as B 0 AT2 [ 10 ]. Based on previously reported IC 50 values [ 30 , 31 , 32 , 44 ], the investigated concentration ranges for the two inhibitors were selected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming poor blood-barrier permeability, the overlap with glutamate transporters described in this work may not be as detrimental in peripheral tissues where glutamate transporters are expressed at a much lower density than within the CNS. 46 Other transporters that should be considered for inhibitor cross reactivity include the neutral amino acid transporters from the SLC38A and SLC7A+SLC3A2 gene families.…”
Section: Discussionmentioning
confidence: 99%